2015
DOI: 10.1007/s00128-015-1671-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wastewater from Oil Exploration on Soil Mesofauna

Abstract: Wastewater from oil exploration may contain substances that can alter the diversity of soil organisms. This study evaluated whether produced water treated by filtration or reverse osmosis and glutaraldehyde from reverse osmosis treatments negatively affected the mesofauna in an irrigated area. In the field, irrigation with produced water treated by reverse osmosis and filtration influenced Hymenoptera and Cosmochthonius sp., while Entomobryomorpha springtails were affected only by the reverse osmosis water. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Soil pollution with petroleum-derived substances (PDSs) entails a strong negative effect on both its physicochemical properties [1,2] and biological activity [3][4][5][6][7], as well as causing far-reaching changes in organisms indirectly exposed to these pollutants (e.g., herbivores) [8][9][10]. The components that are especially dangerous to the environment are polycyclic aromatic hydrocarbons (PAHs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Soil pollution with petroleum-derived substances (PDSs) entails a strong negative effect on both its physicochemical properties [1,2] and biological activity [3][4][5][6][7], as well as causing far-reaching changes in organisms indirectly exposed to these pollutants (e.g., herbivores) [8][9][10]. The components that are especially dangerous to the environment are polycyclic aromatic hydrocarbons (PAHs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…2007;Allen and Robinson 1993). Ferreira et al 2015 andLopes et al 2014 found changes in the mesofauna and in the microbiology composition of soils irrigated with PW.…”
Section: Introductionmentioning
confidence: 99%